A mixed methods study to explore the outcomes, experiences and perceptions of women who attended a new counselling model for HIV-positive pregnant women accessing antenatal services in Khayelitsha, Cape Town, South Africa - Kirya, Viola (Department of Public Health and Family Medicine, 2016)
Objectives: The aim of this study was to explore the experiences and perceptions of counsellors and patients towards a new counselling model for HIV-positive pregnant women on Option B+ at an antenatal clinic in South Africa and to describe the cohort of HIV-positive pregnant women who experienced the new counselling model. Methods: A mixed methods study design was employed. The quantitative data collection involved using retrospective cohort quantitative data of women that were initiated on Option B+ during the period of 1 October 2013 to 30 June 2014. The variables of interest included: age, gravidity, antiretroviral therapy initiation date, viral load result and number of counselling sessions completed. These were obtained from patient folders and from the Department of Health patient electronic health record. The data was analysed using STATA 12. The qualitative data involved semi-structured interviews of patients and counsellors who had experienced the counselling model. Results: The number of women who completed a total of 1, 2, 3 or 4 counselling sessions was 25%, 26%, 48% and 1% respectively. The percentage of women that were retained in care for more than 8 weeks postnatal was 53%. Of the women with VL results, 92% were virally suppressed. The Fisher's exact test showed a P-value of 0.05 at a level of significance of P ≤ 0.05. Therefore there is sufficient evidence to show that there is a positive association between the number of counselling sessions completed and number of postnatal days in care. The study also found that from the counselling, the women gained social support, knowledge about: antiretroviral therapy, HIV, drug side effects and infant feeding. Conclusion: The poor uptake of the counselling intervention includes poor communication, service delivery challenges and social factors. The main motivation for initiating ART and maintaining adherence to treatment was to protect the baby and as a result, some women maintained adherence despite not completing the counselling. Women valued the education that they received during the counselling sessions and this influenced their adherence. Psychosocial support from the counsellors and peers was found to be vital to the women and this highlighted the need to incorporate a support group for the pregnant women, as part of the intervention. The findings also suggest that when offering counselling interventions to pregnant women, a balance between psychosocial support, practical support and patient education needs to be struck. Finally, education of the community on the importance of counselling is important in order to improve the uptake of the counselling because interventions aimed at mothers do not always take into account the influence of the social environment on the uptake of the intervention.